Effect of Fermentation Duration and Glucose Concentration on Organoleptic Characteristics of Hard Candy Glucose Substitution of Coffee Pulp by Fermentation Method - Khairidzi Arsyca Umayya; Marshamada Harvenya Faelassufa; Nurista Ayu Soutul Haqiqi; Laili Fathurrahmah Tiarno; Zefanya Widyasari; Asri Nursiwi (Jurnal Indonesia Sosial Teknologi, 2024)
Coffee pulp is the outer layer of coffee pulp which is one type of waste from the coffee processing process that increases every year without maximum utilization. Coffee pulp contains cellulose (63%) which can be utilized in the manufacture of semi-finished products in the form of liquid sugar through the fermentation method. Phenol in coffee pulp causes a sour and astringent taste in processed products, so a fermentation process is needed to degrade phenol compounds during aerobic fermentation. The purpose of this study was to determine the effect of the length of fermentation of coffee pulp on the phenol content of liquid sugar produced and to analyze the effect of the concentration of liquid sugar fermented from coffee pulp on the organoleptic characteristics of candy in the market. The test of phenol content using the Folin Ciocalteu method and the test of reducing sugar using the Nelson Somogyi method showed that the longer the fermentation process took place, the lower the levels of total phenol and reducing sugar in the juice and coffee pulp sugar produced. Sensory testing with the ranking test on 30 panellists showed that the variation of adding 20% coffee pulp fermented liquid sugar concentration was overall most liked by panellists because it was close to candy products in general with the highest sucrose concentration compared to other candy formulas.